The Oasis of Bukhara, Volume 3 : Material Culture, Socio-territorial Features, Archaeozoology and Archaeometry - Rante, Rocco (Arts and Archaeology of the Islamic World, 2024)
The Oasis of Bukhara, Volume 3: Material Culture, Socio-territorial Features, Archaeozoology and Archaeometry , focuses on the study of material culture (pottery and glass), as well as on the archaeoscience activities that took place during the archaeological mission MAFOUB (2009-2023). The topics in this third, concluding volume concern environmental aspects, preliminary results on archaeozoology, the reconstruction of the evolution of the fauna over nineteen centuries, and politico-territorial aspects. It completes the urban and demographic framework that was presented in the previous two volumes. Contributors: Anne Bouquillon, Jacopo Bruno, Yvan Coquinot, Delphine Decruyenaere, Christel Doublet, Ayano Endo, Nathalie Gandolfo, Takako Hosokawa, Marjan Mashkour, Djamal Mirzaakhmedov, Andrey Omelchenko, Elisa Porto, Silvia Pozzi, Gabriele Puschnigg, Rocco Rante, Pascale Richardin, Yoko Shindo, Toshiyasu Shinmen, Tamako Takeda, Manon Vuillien, Antoine Zink The volume is co-published by Brill, Leiden, and the Louvre Museum, Paris.